2017
DOI: 10.1111/tri.12931
|View full text |Cite
|
Sign up to set email alerts
|

What is the significance of end-stage renal disease risk estimation in living kidney donors?

Abstract: Two end-stage renal disease (ESRD) risk calculators were recently developed by Grams et al., and Ibrahim et al. to calculate ESRD risk before donation among living kidney donors. However, those calculators have never been studied among potential donors for whom donation was refused due to medical contraindications and compared to a group of donors. We compared 15-year and lifetime ESRD risk of donors and nondonors due to medical cause as estimated by those two calculators. Nondonors due to medical cause (n = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Only the calculator by Grams et al [2] provides lifetime (albeit predonation) ESKD risk estimates and is endorsed by KDIGO. We read with interest the publication by Gaillard et al [5], having recently reported similar findings from Australia [6]. Like Gaillard et al, we observed higher predonation 15year risk but similar lifetime ESKD risk in declined compared with accepted LKDC using the Grams calculator.…”
Section: Dear Editorssupporting
confidence: 81%
See 2 more Smart Citations
“…Only the calculator by Grams et al [2] provides lifetime (albeit predonation) ESKD risk estimates and is endorsed by KDIGO. We read with interest the publication by Gaillard et al [5], having recently reported similar findings from Australia [6]. Like Gaillard et al, we observed higher predonation 15year risk but similar lifetime ESKD risk in declined compared with accepted LKDC using the Grams calculator.…”
Section: Dear Editorssupporting
confidence: 81%
“…We wish to emphasize the need for cautious use of the Ibrahim calculator [3] to estimate lifetime risk and highlight the paradoxical effect of donor age. Gaillard et al [5] reported higher 15-year but similar 40-year postdonation risk in their declined versus accepted LKDC using the Ibrahim calculator. As the median age was 10 years older in their declined LKDC, they were likely disadvantaged when 40-year postdonation risk was used to compare their long-term risk with accepted LKDC.…”
Section: Dear Editorsmentioning
confidence: 91%
See 1 more Smart Citation